CHARACTERIZATION OF SULFONATED POLYSULFONE/BENTONITE HYBRID MEMBRANES - Bambang Piluharto; Imam Syafi’i; R. Indahsari; Tanti Haryati (Jurnal ILMU DASAR, 2012)
Sulfonated polysulfone membrane is one of the alternative membranes as replacing Nafion membrane for the fuel cell application. This membrane was prepared by introducing sulfonic group in the polysulfone structure backbone, so that provides the ionic membrane. However, more ionic groups in the SPSF membrane lead to loss mechanical stability. This study aims to prepare the hybrid membrane from SPSF and bentonite. In here, various of bentonite concentrations were used as variable to study water uptake and ion-exchange capacity properties. As the results, increasing bentonite concentrations lead to increase water uptake and ion-exchange capacity. By the functional group analysis, proved that adding bentonite in SPSF did not change structure of SPSF, means that interaction between SPSF and bentonite were physical interactions.